Peningkatan Kualitas Produk Olahan Ikan Bandeng Kemasan Vakum - Herlina Herlina; Siti Mundari (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Delta Presto SMEs is a SMEs that is engaged in the production of processed Bandeng fish. The products sold are fried bandeng fish, presto bandeng fish, bandeng fish brains, smoked bandeng fish. The problems experienced by SMEs are for presto bandeng fish products, the vacuum sealer owned by SMEs is old and often damaged, the suction power is low so the products can not last long, only about 7 to 9 days. The second problem is that the box used as packaging for fried bandeng fish is not laminated so that the oil seeps out of the box and the box packaging becomes oily on the top and bottom. To overcome these problems, a new vacuum sealer was procured and also a packaging design using a laminated box. The results of the new vacuum sealer can make the product last longer between 2 to 3 months because the suction power is stronger, besides that it also speeds up the production process because it can be used to vacuum two packs of pressure bandeng fish. The results of the laminated box design can improve the aesthetic appearance of the fried bandeng fish box